A comparative study of the dorsolateral and ventrolateral approaches for repair of canine sacroiliac luxation - Singh, Harpreet; Kowaleski, Michael P.; McCarthy, Robert J.; Boudrieau, Randy J. (Veterinary and Comparative Orthopaedics and Traumatology, 2016)
Objectives: Retrospective comparison of dorsolateral (DLA) and ventrolateral (VLA) surgical approaches for treatment of canine sacroiliac luxation using three different radiographic analyses.Methods: Surgical cases with immediate and ≥ 4 week postoperative radiographs were reviewed (Jan. 2000 to Jan. 2015). Exactness of reduction, screw position, and sacral body screw purchase were assessed with three separate methods: single plane assessment and orthogonal assessment with or without rotational limits.Results: The reduction index (RI) for DLA and VLA was not significantly different with single plane assessment (p = 0.0789), but it was significantly greater for DLA than VLA with orthogonal assessment, with or without rotational limits (p = 0.0039, p = 0.0146). No differences were observed with screw placement into the intended location (single plane, and orthogonal assessment with or without rotational limits; p = 0.2941, p = 0.4151, p = 0.3550, respectively). No differences were observed between mean screw purchase index (SPI) and the 60% goal for the DLA (p = 0.1303, p = 0.9594, p = 0.7120) or 50% goal for the VLA (p = 0.2224, p = 0.1401, p = 0.2224; single plane, and orthogonal assessment with or without rotational limits). Implant loosening was present in four DLA cases and one VLA case. No differences were observed in the number of cases or number of screws that loosened (p = 0.3483 and p = 0.6873, respectively).Clinical significance: The key factor demonstrated in maintaining screw and fixation stability was correct screw placement within the sacral body, regardless of the surgical approach.
Keywords: Sacroiliac luxation; dorsolateral approach; ventrolateral approach; implant failure